Legal Consequences of Incorrectness in the Declaration of the Presentative in the Inheritance Deed Made by the Notary (Study of Supreme Court Cassation Decision Number: 917 K/Pdt/2025) - Shofa, Jannatu; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
The validity and evidentiary power of an authentic inheritance deed made before a Notary still raises disputes over inheritance deeds where the existence of an authentic deed does not always guarantee a final and binding resolution of inheritance disputes so that this condition creates legal uncertainty, both for the heirs and for the Notary as a public official. The purpose of this thesis research is to determine the legal consequences for the Notary regarding the inaccuracy of the statement of the person appearing in the Notary's inheritance deed, to analyze the judge's considerations regarding disputes over inheritance deeds made authentically before a Notary in decision number: 917 K/Pdt/2025 and to determine the format of an authentic Notary deed of inheritance information based on the provisions in force in Indonesia. The research method applied in this study is normative juridical, utilizing a statute approach and a case approach. The analysis was conducted qualitatively, relying on primary, secondary, and tertiary legal materials. All data were analyzed based on the theory of legal certainty and the theory of responsibility as the research's conceptual framework.